Lights and shadows of NSAIDs in bone healing: the role of prostaglandins in bone metabolism - Lisowska B; Kosson D; Domaracka K (Dove Medical Press, 2018)
Barbara Lisowska,1 Dariusz Kosson,2 Karolina Domaracka3 1Department of Anesthesiology and Intensive Care, John Paul II Western Hospital in Grodzisk Mazowiecki, Grodzisk Mazowiecki, Poland; 2Division of Teaching, Department of Anaesthesiology and Intensive Care, Medical University of Warsaw, Warsaw, Poland; 3Department of Anaesthesiology and Intensive Care, Medical University of Warsaw, Warsaw, Poland Abstract: In this review, we discuss the current data about the anatomy and function of bone tissue with particular regard to influence of prostaglandins. Bone tissue dynamics are characterized by a constant remodeling process that involves all bone tissue cells. The communication between bone component cells and other organs is necessary for bone remodeling equilibrium and confirms the dynamic character of bone tissue. Remodeling is also a vital element of healing processes and in adapting bone tissue to stress responses. Therefore, in our review we present the role and significance of bone cells and signaling pathways enabling maintenance of bone homeostasis and remodeling process stability. Cyclooxygenase (COX) is a crucial enzyme in the production of prostaglandins and thromboxane. We focus on the role of COX isoenzymes with highlighting their connection with bone formation, resorption and repair. Prostaglandins are known as arachidonic acid metabolites acting through specific membrane receptors and play an important role in the regulation of osteoblast and osteoclast functions. Prostaglandin PGE2 with its four defined receptors (EP1R, EP2R, EP3R and EP4R) is crucial to maintain balanced bone turnover. Their stimulatory or inhibitory effects appear to depend on different structure-activity relations and signaling pathways. We have described the role of these receptors in bone metabolism and healing. We conclude that the activity of prostaglandins in bone tissue is defined by maintaining bone remodeling balance and its reactions to humoral mediators and mechanical stress. Most data confirm that among prostaglandins, PGE2 takes part in all processes of trauma response, including homeostasis, inflammation and healing, and plays a key role in bone physiology. Keywords: bone cells and metabolism, COX, prostaglandins